2020
DOI: 10.1590/1678-5150-pvb-6530
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral pyelonephritis due to Escherichia coli infection in a captive jaguar (Panthera onca)

Abstract: Extraintestinal pathogenic Escherichia coli (ExPEC) is a highly diverse pathotype of E. coli which colonizes the intestine, and it is considered an important etiological agent associated with bacteremia and other systemic infections, among them urinary tract infection. Retrospective studies evaluating morbidity and mortality of nondomestic felids have demonstrated that urinary tract diseases are among the main causes of death for geriatric animals. Also, mesenchymal neoplasms of the uterus are common in wild f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…In wild felids, Carvalho et al (5) reported a suppurative hemorrhagic cystitis in an adult male snow leopard (Panthera uncia) caused by an extraintestinal pathogenic Escherichia coli strain. Additionally, Wronski et al (32) reported a case of pyelonephritis due to uropathogenic E. coli in a captive jaguar (Panthera onca). However, in this case, urinary obstruction was caused by association of an inflammatory process and a compressive neoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…In wild felids, Carvalho et al (5) reported a suppurative hemorrhagic cystitis in an adult male snow leopard (Panthera uncia) caused by an extraintestinal pathogenic Escherichia coli strain. Additionally, Wronski et al (32) reported a case of pyelonephritis due to uropathogenic E. coli in a captive jaguar (Panthera onca). However, in this case, urinary obstruction was caused by association of an inflammatory process and a compressive neoplasm.…”
Section: Discussionmentioning
confidence: 99%